Pengaruh Tata Kelola Perusahaan Terhadap Kualitas Laba dengan CSR Sebagai Variabel Intervening - Mas'ud Basyri; Kiryanto Kiryanto (Jurnal Akuntansi Indonesia, 2025)
Abstract This study aims to analyze the influence of the board of commissioners, board of directors, and audit committee on earnings quality, with Corporate Social Responsibility (CSR) as an intervening variable. The sample consists of publicly listed companies included in the LQ-45 index for the 2020–2023 period, selected using the purposive sampling method, resulting in a total of 27 companies. The analyzed data is secondary data obtained from the official websites of the Indonesia Stock Exchange and the sampled companies. Hypothesis testing was conducted using the Partial Least Square (PLS) method. The findings indicate that the board of commissioners has a positive effect on CSR disclosure, while the board of directors has a negative effect. Meanwhile, the audit committee does not influence CSR disclosure. Furthermore, the board of commissioners and the board of directors do not affect earnings quality, whereas the audit committee has a significant impact on earnings quality. This study also finds that CSR negatively affects earnings quality. Overall, the independent variables do not influence earnings quality through CSR disclosure.